Measurement of prompt D+ and D+s production in pPb collisions at √sNN = 5.02 TeV - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Carus, Leon; Caspary, Rowina; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Langenbruch, Christoph; Leverington, Blake; et al. (Journal of high energy physics, 2024)
The production of prompt D+ and D+s mesons is studied in proton-lead collisions at a centre-of-mass energy of √sNN = 5.02 TeV. The data sample corresponding to an integrated luminosity of (1.58 ± 0.02) nb−1 is collected by the LHCb experiment at the LHC. The differential production cross-sections are measured using D+ and D+s candidates with transverse momentum in the range of 0 < pT < 14 GeV/c and rapidities in the ranges of 1.5 < y∗ < 4.0 and −5.0 < y∗ < −2.5 in the nucleon-nucleon centre-of-mass system. For both particles, the nuclear modification factor and the forward-backward production ratio are determined. These results are compared with theoretical models that include initial-state nuclear effects. In addition, measurements of the cross-section ratios between D+, D+s and D0 mesons are presented, providing a baseline for studying the charm hadronization in lead-lead collisions at LHC energies.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Text ist "+" jeweils hochgestellt, "s" tiefgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, M. Borsato, L. Carus, R. Caspary, M. De Cian, G. Frau, G.A. Günther, X. Han, S. Hansmann-Menzemer, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 15.07.2024